Bright Field Microscopy to Detect Decoy Cells Due to BK Virus Infection in the Fresh and Unstained Urine Sediment in Kidney Allograft Recipients - Poloni, José A. T. (J Clin Lab Anal, 2016)
BACKGROUND: BK virus (BKV) may reactivate in kidney allograft recipients ultimately leading to BKV nephropathy and graft loss. Decoy cells (DCs) are one of the early marks of BKV reactivation, and these can be detected in the urine sediment. METHODS: A cohort of 102 kidney transplant patients was followed during months 3 and 6 after the transplant procedure. Urine samples were obtained to detect the presence of DC in the fresh and unstained urine sediment under bright field microscopy (BFM), in concomitance to the determination of the amount of BK viruria by qPCR. RESULTS: Decoy cells were found in 14.7% of patients (15/102). There was a strong agreement (P < 0.001) between qualitative DC detection by two experienced analysts and by qPCR. The positive predictive value, negative predictive value, specificity, and accuracy of BFM were 80%, 75%, 97%, and 75%, respectively. Test sensitivity was 16%. The comparative method was the qPCR. CONCLUSIONS: Despite its limited sensitivity, BFM of unstained urine sediment is an easily available, fast and cheap method to identify DCs in the population of kidney allograft recipients. The diagnostic performance of BFM on the hands of less experienced analysts deserves further investigation.